2006
DOI: 10.21273/horttech.16.1.0030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chloropicrin on Nutsedge Emergence through Polyethylene Mulch

Abstract: Field trials were conducted from 1999 to 2003 to determine whether chloropicrin (Pic) stimulates nutsedge (Cyperus spp.) emergence through polyethylene mulch, and to examine at which Pic rate the stimulatory effect is maximized. Shank-injected Pic rates were 0, 50, 100, 150, 200, and 250 lb/acre. Application rates between 107 and 184 lb/acre of Pic stimulated nutsedge sprouting through polyethylene mulch by 60%, 400%, 58%, and 120% more than the nontreated control during four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…Sprouting, but Pic rate >280 kg ha −1 resulted in similar Cyperus spp. population density compared to the nonfumigated control . Locascio and Dickson observed that Cyperus spp.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Sprouting, but Pic rate >280 kg ha −1 resulted in similar Cyperus spp. population density compared to the nonfumigated control . Locascio and Dickson observed that Cyperus spp.…”
Section: Resultsmentioning
confidence: 98%
“…Previous research has clearly demonstrated that Pic alone is ineffective for Cyperus spp. control . Santos et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under field conditions, Pic at rates ranging from 119 to 206 kg ha −1 can stimulate the Cyperus spp. tuber sprouting . As a result, the addition of Pic may improve the efficacy of the other fumigant in the combination for controlling Cyperus spp .…”
Section: Discussionmentioning
confidence: 99%